PERAN KEPUASAN KERJA DALAM PENGARUH STRUKTUR DAN BUDAYA ORGANISASI TERHADAP KINERJA TENAGA KEPENDIDIKAN - Susrini; Hamidah Nayati Utami; Mohammad Nuh (Jurnal Ilmu Manajemen, 2026)
The transformation of higher education institutions into public universities with legal entity status has driven changes in organizational governance that demand greater professionalism and performance from faculty members. This study offers a unique approach by integrating organizational structure and organizational culture into a single research model that examines employee performance through job satisfaction as a mediating variable. This study aims to analyze the influence of organizational structure and organizational culture on employee performance through job satisfaction. This study employs a quantitative approach using a survey method. The study population consists of academic staff at the university’s central office in Malang, with a sample of 201 respondents selected using random sampling techniques. Data were collected via a questionnaire that had passed validity and reliability tests, then analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that organizational structure and organizational culture have a positive and significant effect on job satisfaction. Organizational structure has a positive but insignificant effect on employee performance, while organizational culture and job satisfaction have positive and significant effects on employee performance. Furthermore, job satisfaction was found to act as a mediator in the relationship between organizational structure and organizational culture and employee performance. This study highlights the importance of strengthening an adaptive organizational structure and a supportive organizational culture in order to sustainably improve job satisfaction and the performance of educational staff.